1999
DOI: 10.1177/000992289903801003
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Controlled Trial of a Liquid Loperamide Product Versus Placebo in the Treatment of Acute Diarrhea in Children

Abstract: This randomized, double-blind, placebo-controlled trial of 48 hours' duration conducted in 13 primary care ambulatory practices in the United States and Mexico was used to compare the efficacy and safety of loperamide with placebo for the treatment of acute diarrhea in children aged 2 through 11 years. Two hundred fifty-eight children with acute nonspecific diarrhea were enrolled. Children were randomly assigned to treatment with loperamide HCl 0.5 mg/5 mL (n = 130) or placebo (n = 128). The first dose of lope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Key researchers in the field did not suggest any additional trials. Of the 91 articles examined, we excluded 34 studies with no control group, 16 studies where children younger than 12 y of age were not included, one study where we were unable to determine the number of children younger than 12 y of age, and 24 studies that did not otherwise meet inclusion criteria, leaving 16 studies that met the four inclusion criteria (Figure 1) [16–31]. We excluded one study because only subanalysis results were presented [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key researchers in the field did not suggest any additional trials. Of the 91 articles examined, we excluded 34 studies with no control group, 16 studies where children younger than 12 y of age were not included, one study where we were unable to determine the number of children younger than 12 y of age, and 24 studies that did not otherwise meet inclusion criteria, leaving 16 studies that met the four inclusion criteria (Figure 1) [16–31]. We excluded one study because only subanalysis results were presented [29].…”
Section: Resultsmentioning
confidence: 99%
“…While four out of 13 studies defined diarrhea resolution as the time to the last unformed stool [16,17,26,31], four studies defined diarrhea resolution as change in stool consistency [22], <15 g of stool/kg/d [24], two or fewer liquid/soft stools/d [18], or return to normal bowel habits [21], and five studies did not report their criteria for diarrhea resolution [19,20,23,25,27]. …”
Section: Resultsmentioning
confidence: 99%
“…Th us, the mechanisms of antidiarrheal eff ect of loperamide are indirect or direct inhibition of mucosal secretion and reduction in motility. In a comparative randomized trial in patients with TD, loperamide reduced the number of diarrheal stools passed when compared with BSS ( 108 ) and loperamide was shown to shorten diarrhea in both children ( 109 ) and adults with acute diarrhea ( 110 ). Th e recommended dose of loperamide for therapy for adults with diarrhea is 4 mg initially followed by 2 mg aft er subsequently Summary of evidence .…”
Section: Recommendationmentioning
confidence: 99%
“…No significant adverse effects were reported, but the group given loperamide had a higher rate of adverse effects, compared with the group given placebo (15% vs. 7%) [22]. An earlier study of a 2-center, placebo-controlled clinical trial conducted in Liverpool, England, and Libya reported no statistically significant differences in the course of gastroenteritis [23].…”
Section: Antimotility Agentsmentioning
confidence: 84%